An experimental study of combustion stability and emissions characteristics of a surface-stabilized combustion burner fueled with natural gas-syngas blends (2019)
The aim of this paper is to investigate the effects of replacing natural gas with synthetic gases on the combustion stability and the combustion pollutants of a surface-stabilized combustion burner. We evaluated three synthetic gases with high hydrogen contents ranging from 60% H2 to 75% H2. The experimental study was carried out under different input power conditions (300 to 500 kW/m2) and equivalence ratios. The results obtained in this work indicate that combustion stability of natural gas in a surface-stabilized combustion burner is significantly affected by the addition of synthetic gases, which in this case was held constant to obtained equimolar mixtures of synthetic gas and natural gas. This result seems to be explained by the variations of some important combustion properties, mainly the laminar burning velocity and the adiabatic flame temperature. On the other hand, it was found that CO emissions slightly decrease with increasing H2 concentration. This behavior is attributed to the increase of the OH radical. © 2019 Published under licence by IOP Publishing Ltd.